THE ROLE OF ARCHITECTURAL DESIGN IN CULTURAL IDENTIFICATION - Raximov Otabek Davlatovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of architectural design in reinforcing cultural identification. It examines how architecture reflects social values, traditions, and heritage while shaping the identity of communities and urban environments. The study highlights that thoughtfully designed buildings and public spaces can strengthen cultural awareness, preserve historical context, and foster a sense of belonging among residents.